Initial clinical experience using the EchoNavigator(®)-system during structural heart disease interventions - Balzer, Jan (World J Cardiol, 2015)
AIM: To present our initial clinical experience using this innovative software solution for guidance of percutaneous structural heart disease interventions. METHODS: Left atrial appendage, atrial septal defect and paravalvular leak closure, transaortic valve repair and MitraClip(®) procedures were performed in the catheter laboratory under fluoroscopic and echocardiographic guidance. The two-dimensional and three-dimensional images generated by the transesophageal echocardiography probe were interfaced with the fluoroscopic images in real-time using the EchoNavigator(®)-system. RESULTS: The application of the novel image fusion technology was safe and led to a better appreciation of multimodality imaging guidance due to improved visualization of the complex relationship between catheter devices and anatomical structures. CONCLUSION: The EchoNavigator(®)-system is a feasible and safe tool for guidance of interventional procedures in structural heart disease. This innovative technology may improve confidence of interventional cardiologists in targeting and positioning interventional devices in order to increase safety, accuracy, and efficacy of percutaneous interventions in the catheter laboratory.